2011
DOI: 10.1097/aci.0b013e328342335f
|View full text |Cite
|
Sign up to set email alerts
|

The crucial role of dendritic cells in rhinitis

Abstract: Several functional dendritic cell studies have been published indicating that there are disease-dependent dendritic cell differences in rhinitis. In addition to these differences, factors like epithelial cells and T cells influence dendritic cells. Several new therapeutic options are available targeting direct or indirect dendritic cell functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Variants with cell-type-specific eQTL effects in the single-cell PBMC (scPBMC) data are enriched for disease-associated variants of nine immune-related traits (hF DR ≤ 5%). For example, variants with eQTL effects specific to conventional and plasmacytoid dendritic cells are enriched for allergic rhinitis-associated variants, consistent with the crucial role of dendritic cells in the development and maintenance of rhinitis [54]. In addition, variants with eQTL effects specific to B and CD4+…”
Section: Resultsmentioning
confidence: 61%
“…Variants with cell-type-specific eQTL effects in the single-cell PBMC (scPBMC) data are enriched for disease-associated variants of nine immune-related traits (hF DR ≤ 5%). For example, variants with eQTL effects specific to conventional and plasmacytoid dendritic cells are enriched for allergic rhinitis-associated variants, consistent with the crucial role of dendritic cells in the development and maintenance of rhinitis [54]. In addition, variants with eQTL effects specific to B and CD4+…”
Section: Resultsmentioning
confidence: 61%
“…However, we cannot eliminate paracellular or cell autonomous movement of prions, as has previously been shown [26], [59]. Inhalation of dust and other particles has been shown to cause rhinitis that enhances cytokines and increases the number of DCs in the nasal mucosa [55], [60][62].…”
Section: Discussionmentioning
confidence: 91%
“…Introduction of carboxyfluorescein succinimidyl ester (CFSE)-labeled DCs or DiY Dye in the nasal mucosa in droplet form resulted in detectable CFSE-labeled DCs and DiY in the nasal mucosa in the nasal-associated lymphoid tissue (NALT) and in the cervical LN, which drains the nose. No CFSE-labeled cells could be detected in either the mediastinal LN or the lung (35). In a human migration study of the respiratory tract, it is indicated that antigen pulsed DCs that are introduced by injection in the nasal inferior turbinates can be traced back to the regional LNs (36).…”
Section: Migration From Peripheral Tissue To the Draining Lnmentioning
confidence: 99%